Occipitocervical fixation: A case report of our techniques and results - Sakti, Yudha Mathan; Lanodiyu, Zikrina Abyanti; Wijanarko, Sonny; Alhaq, Zaky Asad; Sakadewa, Galih Prasetya; Ahmad, Husein; Desfiandi, Prisilla; Magetsari, Rahadyan (Elsevier Ltd, 2022)
Introduction: Occipitocervical fixation (OCF) can provide good fusion rate to treat various craniovertebral junction (CVJ) pathologies. Biomechanically it gives rigid fixation, good fusion rate, and allows for effective decompression. However, rigid fixation on the mobile occipitocervical junction has shortcomings that affect the post-operative clinical functional outcomes and range of motion. This study aimed to evaluate and elaborate the functional outcomes, range of motions, and radiographic findings in our patients underwent OCF. Case report: We presented a report of 3 patients underwent posterior decompression procedure followed by occipitocervical fixation. All three patients' clinical outcome was assessed clinically by, Japanese Orthopaedic Association (JOA) score and grading, Karnofsky, range of motion and radiographic cervical alignment evaluation parameters. Result: All patients have seen improvement (minimal 1 grade in JOA and >30 points of Karnofsky score) in 3 months after the procedure, had a tolerable range of motion limitation, normal range of cervical lordotic and cervical brow vertebral angle (CBVA). Unfortunately, one patient with loss of cranial fixation may be related to history of infection and lack of post-operative wound care. Conclussion: Our cases conclude that Occipitocervical fixation is a safe technique that provides excellent fusion rate with good functional outcome and tolerable range of motion limitation. Due to its unique anatomy and technically demanding, serial post-operative monitoring evaluation of this procedure is paramoun